2022
DOI: 10.3390/microorganisms10091709
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Substrates on the Morphological Features and Polyols Production of Endomyces magnusii Yeast during Long-Lasting Cultivation

Abstract: The study on the influence of different glucose concentrations (2%, 0.5%, and 0.2%) and glycerol (1%) on the morphological and physiological features, as well as the composition of soluble carbohydrates, was performed using Endomyces magnusii yeast. Two-factor analysis of variance with repetitions to process the data of the cell size changes showed that the substrate type affected cell size the most. The cells with 2% glucose were 30–35% larger than those growing on glycerol. The decrease in the initial glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…The study of the soluble cytosol carbohydrates profile of the E. magnusii yeast upon CR showed that cultures using 2% glucose and 1% glycerol contained mainly arabitol and mannitol. However, at low glucose concentrations they were substituted by inositol [10].…”
Section: Roberts and Hudsonmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of the soluble cytosol carbohydrates profile of the E. magnusii yeast upon CR showed that cultures using 2% glucose and 1% glycerol contained mainly arabitol and mannitol. However, at low glucose concentrations they were substituted by inositol [10].…”
Section: Roberts and Hudsonmentioning
confidence: 99%
“…The composition of soluble cytosol carbohydrates in the yeast may include glucose and fructose, as well as polyols, namely arabitol, mannitol, trehalose, inositol, glycerol [10], accumulated in the cell vacuoles (Figure 1D,E). All this makes E. magnusii an attractive object for biotechnology, however, the data on this yeast application in biotechnological processes are quite limited.…”
Section: Introductionmentioning
confidence: 99%
“…The pseudomycelium that is characteristic of this species (described by Limtong [19]) can be observed with glucose (Figure 1a) but not with glycerol (Figure 2a) as the substrate. There are yeasts that form pseudohyphae when cultivated with some substrates [30] and stress factors, the la er of which include a scarcity of the source of carbon or nitrogen, the presence of certain alcohols, osmotic shock, oxidative stress, and environmental extremes (e.g., in relation to pH and/or temperature) [31]. Although it is not known why CW presently exhibit pseudomycelium growth when cultivated in glucose and unicellular growth in glycerol, these results are in agreement with those reported for Yarrowia lipolytica, a yeast with biotechnological potential.…”
Section: Detection Of Lipids By Confocal Laser Scanning Microscopy (C...mentioning
confidence: 99%
“…Yeasts are eukaryotic organisms that differ in size and shape depending on growth nutrients and environments [27]. The cell size or morphology of Endomyces magnusii [28], Candida utilis ATCC 9950, and Saccharomyces cerevisiae [29] varied when yeast cells were cultivated in the presence of different types and concentrations of substrates. In this study, the correlation between the yeast morphology of M. spicifer SPB2 and its CBL transesterification activity was observed.…”
Section: Morphological Observation Of M Spicifer Spb2mentioning
confidence: 99%